2009
DOI: 10.1007/s12010-009-8864-9
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of α-Amylase from Peel of Citrus sinensis cv. Abosora

Abstract: alpha-Amylase activity was screened in the peel, as waste fruit, of 13 species and cultivars of Egyptian citrus. The species Citrus sinensis cv. Abosora had the highest activity. alpha-Amylase AI from Abosora peel was purified to homogeneity using anion and cation-exchange, and gel filtration chromatographies. Molecular weight of alpha-amylase AI was found to be 42 kDa. The hydrolysis properties of alpha-amylase AI toward different substrates indicated that corn starch is the best substrate. The alpha-amylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…2C showed that amylolytic activity of germinated seeds from oat (A. sativa) preserve more than 70% of its maximum activity in the range of pH of 5-7 with an optimum observed at pH 5.6. In the other hand, the same optimum pH was described for amylase extracted from the peel of Citrus sinensis [39].…”
Section: Optimum Phmentioning
confidence: 57%
See 1 more Smart Citation
“…2C showed that amylolytic activity of germinated seeds from oat (A. sativa) preserve more than 70% of its maximum activity in the range of pH of 5-7 with an optimum observed at pH 5.6. In the other hand, the same optimum pH was described for amylase extracted from the peel of Citrus sinensis [39].…”
Section: Optimum Phmentioning
confidence: 57%
“…␣-Amylases are generally active in the pH range from 5.5 to 8, but exceptions exist on both sides, mainly for enzymes of microbial origin [11,39]. In this study, the amylase activity was measured at different pHs ranged from 3.6 to 10.5.…”
Section: Optimum Phmentioning
confidence: 95%
“…Citrus fruit is one of the commercial crops in the Egyptian market (Mohamed et al 2010). Orange juice is one of the most consumed beverages today (Martin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature and thermal stability of amylase from O. ficus‐indica seeds were higher than any other plant amylase reported so far except the α‐amylase of Korean pine seeds . The optimum temperature of α‐amylase from finger millet, wheat and peel of Citrus sinensis were reported to be 45–50, 40 and 40–50 °C, respectively …”
Section: Resultsmentioning
confidence: 75%